Anti-viral Activity of 62 Medicinal Plants, Herbs and Spices Available in Bangladesh: A Mini Review (Dhaka University Journal of Pharmaceutical Sciences, 2023)
Microorganisms can cause devastating diseases leading to a pandemic, such as COVID-19 which has created a devastating situation throughout the world. The SARS-CoV-2 or severe acute respiratory syndrome coronavirus-2 is the major concern for creating this pandemic situation. Viruses are the major pathogenic microorganisms that have the potential to be detrimental to human beings and animals in many ways. By entering the human body through different routes and commanding different machinery of the body to generate a higher number of their genomic copies and proteins they create pathogenesis. Phytomedicines may act as suitable weapons to halt the reproduction of such viruses and combat diseases caused byBangladesh is the habitat of about 500 medicinal and aromatic plants. Many of these plants have been found to show anti-viral activity. The anti-viral activity of Terminalia chebula, a well-known Bangladeshi medicinal plant has been proven to combat Newcastle Disease virus, Herpes Simplex Virus, Adenovirus type 5, Measles virus, Echovirus type 11, Rotavirus, Influenza A virus, Hepatitis B virus and Enterovirus. This review article was aimed to search available medicinal plants as novel anti-viral drugs.Dhaka Univ. J. Pharm. Sci. 22(2): 213-232, 2023 (December)